2005
DOI: 10.1016/j.immuni.2004.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the Endothelial Oxidase AOC3 Leads to Abnormal Leukocyte Traffic In Vivo

Abstract: Leukocyte migration from the blood to tissues is a prerequisite for normal immune responses. We produced mice deficient in an endothelial cell-surface oxidase (amine oxidase, copper containing-3 [AOC3], also known as vascular adhesion protein-1 [VAP-1]) and found that this enzyme is needed for leukocyte extravasation in vivo. Real-time imaging shows that AOC3 mediates slow rolling, firm adhesion, and transmigration of leukocytes in vessels at inflammatory sites and lymphoid tissues. Absence of AOC3 results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
136
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 116 publications
(153 citation statements)
references
References 42 publications
15
136
2
Order By: Relevance
“…Co-cultures were incubated in culture medium for 3 days and pulsed with 3 H-thymidine (1 mCi [0.037 MBq] per well) for the final 6 h. Cells were harvested using semi-automated plate harvester (Tomtech MACH III) and counted with the 1450 Microbeta counter (Wallac). The Ab titers against OVA were determined by ELISA as described [31]. The phenotype analyses were carried out as explained above.…”
Section: Immunizationsmentioning
confidence: 99%
“…Co-cultures were incubated in culture medium for 3 days and pulsed with 3 H-thymidine (1 mCi [0.037 MBq] per well) for the final 6 h. Cells were harvested using semi-automated plate harvester (Tomtech MACH III) and counted with the 1450 Microbeta counter (Wallac). The Ab titers against OVA were determined by ELISA as described [31]. The phenotype analyses were carried out as explained above.…”
Section: Immunizationsmentioning
confidence: 99%
“…VAP-1-dependent leukocyte trafficking has been shown so far only in three inflammatory conditions (peritonitis, arthritis and mucosal vaccination) using VAP-1 deficient mice in vivo [21][22][23]. The role of VAP-1 in two mechanistically different and clinically relevant models, IRI and remote organ injury caused by systemic inflammation, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the antibodies do not inhibit the enzymatic activity of VAP-1 and the SSAO inhibitors do not affect the surface epitopes of the molecule seen by the neutralizing antibodies [19,20]. Thus, VAP-1 is envisaged to have both enzyme-activity-dependent and enzyme-activity-independent functions in supporting leukocyte-endothelial interactions.VAP-1-dependent leukocyte trafficking has been shown so far only in three inflammatory conditions (peritonitis, arthritis and mucosal vaccination) using VAP-1 deficient mice in vivo [21][22][23]. The role of VAP-1 in two mechanistically different and clinically relevant models, IRI and remote organ injury caused by systemic inflammation, remains unknown.…”
mentioning
confidence: 99%
“…To generate mTIEhVAP-1-transgenic/VAP-1-knockout (VAP KO+TG) mice, mTIEhVAP-1 line E35 mice expressing human VAP-1 on the vasculature [38] were crossed to VAP-1-knockout mice that were previously created by using conventional gene targeting techniques to replace the mouse VAP-1 gene with a nonfunctional mutant allele [11]. The mTIEhVAP-1-transgenic, mouse VAP-1 mutant allele and endogenous mouse VAP-1 allele were all identified by PCR screening of purified genomic DNA with specific primers and verified immunohistochemically with human and mouse VAP-1 antibodies [38].…”
Section: In Vivo Peritonitis Model For Transmigrationmentioning
confidence: 99%
“…In addition to this, VAP-1 knockout mouse models have shown that lack of the protein leads to increased rolling velocity and a decreased rate of leukocyte transmigration [11]. Recent work has also demonstrated that VAP-1 functions as a regulator of neutrophil transmigration [12].…”
Section: Introductionmentioning
confidence: 98%